Primary Physical Science Education An Imaginative Approach to Encounters with Nature - Fuchs, Hans U. (Springer Nature, 2024)
This open access book is the first of two volumes that integrates a study of direct encounters with Primary Forces of Nature, Wind, Light, Rain, Heat and Cold, Water, etc., with imaginative narrative forms of communication. The approach developed in this book shows how the growth of cognitive tools (first of mythic and then of romantic forms of understanding) lets children make sense of experiencing physical phenomena. An in-depth description of Fluids, Gravity, and Heat as Basic Forces shows how primary sense-making can evolve into understanding of aspects of physical science, allowing for a nature-based pedagogy and application to environmental systems. The final chapter introduces visual metaphors and theatrical storytelling that are particularly useful for understanding the role of energy in physical processes. It explores how a mythic approach to nature can inform early science pedagogy. This book is of interest to kindergarten and primary school teachers as well as early education researchers and instructors.